Effect of Household detergents (Surfactants)Degraded through aquatic fungi - Chaturvedi, Amiy Dutt; Tiwari, K L (Recent Research in Science and Technology, 2013)
Commercial household detergents are diverse group of chemical that is best known for their wide used in laundry industries and household cleaning product. After use, residuals (Surfactant) detergents are discharge into sewage system directly or indirectly into the surface water and most of them end up dispersed into the different environment compartment of soil and water.”Water is facing lots of problems due to domestic waste. These toxic effects of surfactant damaging biodiversity of aquatic environment. Most of aquatic microorganism develops a bio-mechanism for degradation of harmful heavy metals discharge in water at high level. As we know that aquatic environment specially water “fungi” have excellent potential for metal accumulation, particularly genera of Rhizopus, Aspergillus, Streptoverticillum, Sacchromyctes. In general most of commercial household (Surfactants) detergents are biodegradable and amount of it can be commerciallyreduced by secondary treatment of Municipal sewage waste water plants. These discharge waste water pollutants with massive quantities especially surfactant could be a serious threat to aquatic ecosystem. Future studies of Commercial Surfactant toxicities and biodegradation are necessary to withdraw high toxic and non-biodegradableheavy metal for commercial use as a result makes an eco-friendly environment.